The conservation technique of heritage building take place in Malaysia: a case study at Sultan Suleiman Royal Mosque, Selangor / Nur Zafirah Zainal and Izzat Anuar - Zainal, Nur Zafirah; Anuar, Izzat (2023)
Heritage is described as the meaning attached to the past in the present. However, there are several heritage buildings that have been abandoned and are in poor condition. Aside from that, there are also heritage buildings and memorial statues that have already collapsed and failed structurally as a result of our modernisation. Therefore, the objectives of this paper are to investigate the techniques of conversation of heritage buildings in Malaysia and to appreciate the significance of heritage buildings in Malaysia. In order to achieve these objectives, a case study of a significant building with a long history and rich culture in Selangor that has successfully gone through a conservation process will be involved. This research will be produced using systematic data, which will include primary and secondary data. The primary data will be collected based on library-based research focusing on materials such as books, journals, articles and thesis papers. The secondary data will be collected by internet-based resources, including government publications, Non-governmental Organization (NGO) websites and archived news. Site observation and interviews will also be included in this research. The findings from this research project show that repair and preservation techniques are used for the main building. While the restoration techniques were used for the ablution wing.